Chemical reduction of carboxyl groups in heparin abolishes its vasodilatory activity - Paredes-gamero, Edgar J.; Medeiros, Valquíria P.; Lima, Marcelo A.; Accardo, Camila M.; Farias, Eduardo H.C.; Sassaki, Guilherme L.; Campana, Patricia Targon [UNESP]; Miranda, Antonio; Ferreira, Alice T.; Tersariol, Ivarne L.S.; Nader, Helena B. (Wiley, 2012)
Previous studies have shown that heparin induces vascular relaxation via integrin-dependent nitric oxide (NO)-mediated activation of the muscarinic receptor. The aim of this study was to identify the structural features of heparin that are necessary for the induction of vasodilatation. To address this issue, we tested heparin from various sources for their vasodilatation activities in the rat aorta ring. Structural and chemical characteristics of heparin, such as its molecular weight and substitution pattern, did not show a direct correlation with the vasodilation activity. Principal component analysis (PCA) of circular dichroism (CD), 1H-nuclear magnetic resonance (NMR) and vasodilation activity measurements confirmed that there is no direct relationship between the physico-chemical nature and vasodilation activity of the tested heparin samples. To further understand these observations, unfractionated heparin (UFH) from bovine intestinal mucosa, which showed the highest relaxation effect, was chemically modified. Interestingly, non-specific O- and N-desulfation of heparin reduced its anticoagulant, antithrombotic, and antihemostatic activities, but had no effect on its ability to induce vasodilation. On the other hand, chemical reduction of the carboxyl groups abolished heparin-induced vasodilation and reduced the affinity of heparin toward the extracellular matrix (ECM). In addition, dextran and dextran sulfate (linear non-sulfated and highly sulfated polysaccharides, respectively) did not induce significant relaxation, showing that the vasodilation activity of polysaccharides is neither charge-dependent nor backbone unspecific. Our results suggest that desulfated heparin molecules may be used as vasoactive agents due to their low side effects. J. Cell. Biochem. 113: 1359–1367, 2012. © 2011 Wiley Periodicals, Inc.